ASSOCIATION BETWEEN EARLY BILIARY DRAINAGE AND MORTALITY IN PATIENTS WITH ACUTE CHOLANGITIS - Julia O. Fuss; Valeriy V. Boiko; Anna O. Voloboyeva; Viсtor P. Polyovyy (Клінічна та профілактична медицина)
Introduction. Acute cholangitis (AC) is a medical condition that needs to be treated right away with biliary drainage (BD), IV fluids, and antibiotics. Prompt use of antibiotics and drainage of the biliary system are essential components of management as per Tokyo Guidelines 2018 [3]. Three principal drainage procedures are endoscopic biliary drainage (EBD), percutaneous trans-hepatic biliary drainage (PTBD) and surgical biliary drainage [3]. Any delay in diagnosis or initiation of antibiotics and drainage leads to life-threatening consequences. When BD is optimally performed remains uncertain.